Activist Forest Monks, Environmental Adult Education and the Construction of Civil Society in Thailand - Pierre Walter (Adult Education Research Conference, 2006)
Situated at the intersection of adult learning in social movements, the construction of civil society, and environmental adult education, the grassroots movement of Buddhist “forest monks” in Thailand has much to teach us. This paper charts the movement’s history, philosophy, and practice in the construction of Thai civil society.
Keywords: Social movements; environmental adult education